Straightforward synthesis of iron cyclopentadienone N-heterocyclic carbene complexes. Issue 44 (21st October 2015) - Cingolani, Andrea; Cesari, Cristiana; Zacchini, Stefano; Zanotti, Valerio; Cassani, Maria Cristina; Mazzoni, Rita
Abstract : Silver–NHC transmetallation to iron complexes leads to a novel class of easily prepared iron NHC complexes. Abstract : Novel iron complexes bearing both cyclopentadienone and N-heterocyclic carbene ancillary ligands were obtained by a straightforward synthesis from Fe2 (CO)9 . The preparation represents a rare example of silver transmetallation involving iron. The reaction is general and occurs in the presence of variously functionalized NHC and cyclopentadienones.